Reassessment of the current iron deficiency definition in pulmonary hypertension - Reiser, Aurelia Elena; Thiersch, Markus; Gassmann, Max; Muckenthaler, Martina; Geiser, Thomas; Lichtblau, Mona; Ulrich, Silvia (Pulmonary circulation, 2025)
Iron deficiency (ID) is prevalent in pulmonary hypertension(PH), but there is no consensus on ID definition and its possible correlation to prognostic markers. Hence, in this study, PH-patients were recruited at the University Hospital Zurich from May 2019 to April 2021. Clinical and hemodynamic characteristics were recorded at inclusion and venous blood samples were taken. ID was defined as: (i) ferritin-ID: ferritin< 100 µg/L or 100-299 µg/L plus a transferrin saturation (TSAT) < 20%; (ii) TSAT-ID: a TSAT < 20% (males)/< 15% (females) and (iii) TFRI-ID: a transferrin receptor index (TFRI) > 3.2/ > 2.0 depending on CRP < / > 5 mg/L. 94 patients (52% female, mean age 62.9 ± 14.6 years) with pulmonary arterial hypertension(48%), PH associated with lung disease (20%) or chronic thromboembolic PH (32%) were included. Sixty-seven percent fulfilled criteria for ferritin-ID, 35% for TSAT-ID, and 13% for TFRI-ID. Mean pulmonary arterial pressure (mPAP) was elevated in TFRI-ID patients compared to non-ID (50 ± 12.2 mmHg vs. 35.9 ± 11.7 mmHg); however, after correction for age, sex, PH-type, and anticoagulation, the difference was nonsignificant (p = 0.085). NT-proBNP was significantly higher in TFRI-ID-positive (1237 ± 1166 pg/mL vs. 334 ± 417 pg/mL, p = 0.004). No significant differences were found for ferritin-ID and TSAT-ID (p > 0.05). Six-minute walk distance (6MWD) was reduced for both TSAT-ID (402 ± 133 m vs. 469 ± 152 m, p = 0.006) and TFRI-ID (370 ± 112 m vs. 459 ± 151 m, p = 0.052), but not for ferritin-ID (p > 0.05). In conclusion, TFRI-ID is seemingly associated with clinical markers of right heart parameters and disease severity. This could not be seen with the currently recommended ferritin-ID-definition or TSAT-ID. More data is needed to assess the use of the TFRI-ID instead of the ferritin-ID-definition as a method to identify PH-patients at risk and as a threshold for iron substitution.